Contrapassi in Fifteenth-century Italian Dance Reconsidered (Review Response) - Wilson, David (Edinburgh: Edinburgh University Press, 2006)
RESUMEN: In their exhaustive survey of contrapassi and "doppi on one foot" in fifteenth-century Italian balli in the last volume of Dance Research, Lo Monaco and Vinciguerra present a novel and thought-provoking model for the development of these puzzling steps. Its great value lies in opening up new ways of looking at the detailed organisation of step in such dances; but whether this has any relevance to contrapassi is quite another matter, and many will remain sceptical.